MARRIAGE PRACTICUM IN SCHOOL FROM THE PERSPECTIVE OF HADITH STUDIES - Nugroho, Rahmat; Nafila, Radifa Isnain; Nasrulloh, Nasrulloh (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
The Implementation of Fiqh Learning in View of its Practice: Marriage Practicum in Schools as a Learning Material Appears to Require Further Examination, as there are Hadiths that explain the significance of divorce, marriage, and reconciliation, even when conducted in jest and not in earnest. Based on this objective, the researcher utilized a qualitative descriptive methodology. The data collection technique employed was a literature review (library research) with a Hadith study approach that focused on relevant subjects. This study aimed to examine how the marriage practicum is implemented in schools, the Hadith study related to it, and the Islamic legal perspectives. The findings of this study indicate that the marriage practicum occurring in schools involves a simulation of marriage conducted by students. The analysis of these Hadiths reveals their weak authenticity (Dhaif). Despite their weakness (Dhaif), historical accounts suggest that the companions of the Prophet Muhammad practiced the matan of these Hadiths. From an Islamic legal perspective, the simulated marriages conducted by students in schools are not valid due to the absence of a crucial requirement, namely the presence of a guardian (wali). A plausible solution, apart from direct simulation, lies in organizing educational sessions through various institutions, both from the Office of Religious Affairs (KUA) and other relevant bodies. For practical assessments in Islamic jurisprudence classes in schools, these could be redirected towards alternate simulations, such as practical exercises involving the ritual of bathing and shrouding the deceased, the pilgrimage rituals of Hajj and Umrah, religious observances such as Salah (prayer), purification rituals like Tayammum and Wudu (ablution).[Implementasi dari pembelajaran fikih dilihat dari praktiknya. Praktikum pernikahan di sekolah sebagai bahan pembelajaran nampaknya perlu dikaji lebih mendalam, sebab terdapat hadis yang menjelaskan bahwa peristiwa menalak, menikahkan dan rujuk hukumnya berlaku meskipun dilakukan secara gurauan dan tidak sungguh-sungguh. Berdasarkan objektif ini peneliti menggunakan metodologi deskriptif kualitatif. Teknik pengumpulan data yang penulis gunakan adalah metode telaah pustaka (library research) dengan pendekatan kajian hadis yang objeknya relevan dengan pembahasan masalah. Penelitian ini bertujuan untuk mengkaji bagaimana penerapan praktikum pernikahan di sekolah? bagaimana kajian hadisnya? Bagaimana keterangan hadis dan perspektif hukum Islam? Hasil dari kajian ini menunjukkan bahwa praktikum pernikahan yang terjadi di sekolah merupakan simulasi pernikahan yang dilakukan oleh para siswa. Hasil kajian hadis ini menunjukkan bahwa hadis ini Dhoif. Meskipun hadis ini Dhoif, namun dalam praktiknya para sahabat mengamalkan kandungan hadis tersebut. Dalam perspektif hukum Islam, simulasi pernikahan yang dilakukan oleh para siswa di sekolahan tidaklah sah. Karena di dalamnya terdapat syarat yang belum terpenuhi yaitu keberadaan wali. Solusi yang dapat diambil selain melakukan simulasi langsung adalah dengan mengadakan penyuluhan melalui berbagai lembaga baik dari KUA (Kantor Urusan Agama) maupun dari berbagai badan yang terkait. Untuk ujian praktik pada pelajaran fikih di sekolah bisa dialihkan pada simulasi yang lain seperti praktik proses memandikan dan mengafani jenazah, praktik haji dan umrah, praktik ibadah seperti salat, praktik bersuci seperti tayamum dan wudu].